2014
DOI: 10.1103/physrevb.89.064511
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of superconducting transition temperature due to antiferromagnetic spin fluctuations in iron pnictides LaFe(As1xPx)(

Abstract: Systematic31 P-NMR studies on LaFe(As1−xPx)(O1−yFy) with y=0.05 and 0.1 have revealed that the antiferromagnetic spin fluctuations (AFMSFs) at low energies are markedly enhanced around x=0.6 and 0.4, respectively, and as a result, Tc exhibits respective peaks at 24 and 27 K against the P substitution for As. This result demonstrates that the AFMSFs are responsible for the increase in Tc for LaFe(As1−xPx)(O1−yFy) as a primary mediator of the Cooper pairing. From a systematic comparison of AFMSFs with a series o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 35 publications
10
33
0
2
Order By: Relevance
“…In ref. [12], some of the present authors have shown that the variation of λ against the bond angle α exhibits a double dome feature as in Fig.2, which is consistent with the experimental observations 7,8,10 . There, the origin of the double dome structure has been explained as follows: superconductivity is suppressed when the bond angle is increased from α ∼ 110 because the hole Fermi surface around (π, π) originating from the d xy orbital vanishes.…”
Section: A Bond Angle Dependencesupporting
confidence: 80%
See 3 more Smart Citations
“…In ref. [12], some of the present authors have shown that the variation of λ against the bond angle α exhibits a double dome feature as in Fig.2, which is consistent with the experimental observations 7,8,10 . There, the origin of the double dome structure has been explained as follows: superconductivity is suppressed when the bond angle is increased from α ∼ 110 because the hole Fermi surface around (π, π) originating from the d xy orbital vanishes.…”
Section: A Bond Angle Dependencesupporting
confidence: 80%
“…As described in the Introduction, it was found in the NMR experiments 8,16 that the correlation between T c and the development of 1/T 1 T at low temperatures is material dependent. In ref.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the disappearance of superconductivity and a steep rise of Tc in the vicinity of the second superconducting phase implies the second superconducting phase may have a different mechanism behind superconductivity from the first superconducting phase. A two-dome structure in Tc has also seen in the iron pnictide superconductors such as LaFeAs(O1-xHx) [49][50][51]. In the phase diagram of LaFeAs(O1-xHx) (0 ≤ x ≤ 0.6), the first superconducting dome (0.05 ≤ x ≤ 0.20) with a maximum Tc of 29 K and the second dome (0.20 ≤ x ≤ 0.42) with a maximum Tc of 36 K appear with two antiferromagnetic phases (x < 0.05 and 0.4 < x) [49].…”
Section: Isovalent Substitution Effect On Bati 2 Pn 2 Omentioning
confidence: 99%